Industrial Structure, the Flexibility of Working Hours, and Women's Labor Force Participation - King, Allan G. (The Review of Economics and Statistics, 1978)
THIS paper emphasizes the role of the industrial structure of labor demand, as it influences the array of hours of work from which women can choose, as a factor affecting labor force participation rates of women. While the rapid increase in women's labor force participation' has received a great deal of attention from economists (Long, 1958; Mincer, 1962), and the cross-sectional variation also has been studied intensively (Cain, 1966; Bowen and Finegan, 1969; Cain and Watts, 1973; Schultz, 1974), approaches to this topic have stressed micro influences and, since Mincer's influential work, have attached primary importance to obtaining consistent estimates of the income and substitution effects of conventional price theory. Recently, however, writers (Dickinson, 1974; Heckman, 1974) have suggested that in many contexts this approach should be modified to reflect the discrete set of choices workers actually face in the labor market. The manner in which this observation affects the present analysis can best be appreciated if we briefly consider the discussion of the labor supply decision found in the usual textbook analysis of the problem (e.g., Fleisher, 1970 and Rees, 1973). The conventional view is that the woman's market-determined wage sets the rate at which she can trade off leisure, usually taken to represent all non-market uses of time, for income. The representative individual is then assumed to compare her rate of substitution between income and leisure to the market rate, and to allocate that quantity of time to the market that equates the subjective and market rates of substitution at the margin. Nonparticipants in the labor force are assumed to be those women for whom the subjective rate of substitution between income and leisure exceeds the market rate at all potential levels of labor supply, during the period under study. A feature of this analysis that seems particularly objectionable is the assumption that the set of market opportunities allows for a continuous range of choice of the quantity of labor to be supplied, from, say 0 to 60 hours per week, at a relatively constant wage. This is clearly contrary to the facts. For example, a recent analysis of the data gathered for the University of Michigan's Panel Study of Family Income Dynamics (Dickinson, 1974) reports that less than 20% of all workers interviewed were free to optimize their work hours without significant reductions in their wage rates. While it may be true that the conceptual ideal of the continuous range of opportunities could be approximated by an individual choosing among a variety of occupations and industries, this is likely to apply only before many career and personal decisions have been made. With the passage of time, many of what were once decision variables to an individual, such as educational attainment, marital status, and family size, are likely to have become parameters that now serve to define the range within which choice can be exercised. For many women, the labor market in which they work can reasonably be viewed as such a constraint and the industrial structure of that Received for publication December 31, 1976. Accepted for publication May 12, 1977. * University of Texas at Austin. This report was prepared for the Office of the Assistant Secretary for Policy, Evaluation and Research, U.S. Department of Labor, under contract/purchase order no. B9J6-389 1. Since contractors conducting research and development projects under Government sponsorship are encouraged to express their own judgment freely, this report does not necessarily represent the official opinion or policy of the Department of Labor. The contractor is solely responsible for the contents of this report. IBetween 1900 and 1970 the labor force participation rates of women increased from 20% to 40%. A major component of this increase was among women with children. Participation rates for mothers with children under 6 increased over 150% between 1950 and 1972, while rates for mothers with children between 6 and 17 increased by over 60% during the same period.